Pengaruh Strategi Pembelajaran Inkuiri dan Discovery terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Biologi Siswa pada Topik Bioteknologi di MAN I Padang Sidempuan - Batubara, Anni Erlina; Hasruddin, Hasruddin; Mulyana, Rahmat (Magister Pendidikan Biologi, Universitas Negeri Medan, 2016)
This research was aimed to determine: (1) the effect of inquiry learning strategies to students critical thinking skills; (2) the effect of inquiry learning strategies to student learning outcomes; (3) the effect of discovery learning strategies to students critical thinking skills; (4) the effect of discovery learning strategies to student learning outcomes; and (5) the relationship with the critical thinking skills of student learning outcomes. This research was conducted in MAN I Padangsidimpuan, in class XII IPA second semester of the school year 2013/2014 in the matter of Biotechnology. Samples taken consisted of three experimental class. Sample was conducted by cluster random sampling method. This research method was a quasi-experimental techniques Anacova analysis (analysis of covariance) at significance level Î± = 0.05. The results of this study showed that: (1) there are significant inquiry learning strategies to students critical thinking skills (F-count = 4.621; Sig. = 0.036); (2) there are significant inquiry learning strategy on learning outcomes of students (F-count = 2.860; Sig. = 0.018); (3) there are significant discovery learning strategy toward critical thinking ability of students (F-count = 48.709; Sig. = 0,000); (4) there are significant discovery learning strategies students (F-count = 4.034; Sig. = 0,049); and (5) there is a relationship with the critical thinking skills of student learning outcomes using a strategy of inquiry learning, discovery and conventional (F-count = 50.956; Sig. = 0.000).